Effect of 5′‐inosine monophosphate (IMP) and 5′‐guanosine monophosphate (GMP) on the growth, immunity and muscle composition of turbot, Scophthalmus maximus (Linnaeus, 1758). (17th April 2018) - Li, M.; Chen, Y.; Xia, S.; Zhao, W.; Li, N.; You, H.; Yang, L.; Wang, X.; Rajkumar, M.; Geng, X.
Abstract: We evaluated the effect of different concentrations of 5′‐inosine monophosphate (IMP) and 5′‐guanosine monophosphate (GMP) on the growth, immunity and muscle composition of turbot Scophthalmus maximus . Eight diets (containing no IMP or GMP, or 0.5 g/kg IMP, 1.0 g/kg IMP, 2.0 g/kg IMP, 0.5 g/kg GMP, 1.0 g/kg GMP, 2.0 g/kg GMP, or 0.5 g/kg IMP plus 0.5 g/kg GMP) were prepared. A total of 360 fish (average body weight of 105 g) were randomly selected and placed in groups into 24 plastic aquaria (8 treatments × 3 replicates × 15 individuals per plastic aquaria). The tanks were maintained at the temperature of 15 ± 2°C. The experimental diets were fed for 60 days. The specific growth rate (SGR) was significantly higher in S. maximus fed with IMP or GMP compared with fish fed neither IMP nor GMP. The highest SGR was observed in fish fed with 1.0 g/kg IMP. Supplementation with these dietary nucleotides had a positive, but not significant effect on the activity of superoxide dismutase, alkaline phosphatase and acid phosphatase. There was a significant difference in the moisture and crude lipid content of muscle from S. maximus fed the different diets compared with control fish. The highest moisture content was 83.44 for a diet of 0.5 g/kg IMP plus 0.5 g/kg GMP, which was also significantly higher when compared to fish fed alternative diets. The crude lipid content of S. maximus fed diets containing either IMP or GMP was significantly higher than those fed diets without IMP or GMP. Thus, according to these results, the optimal level of dietary IMP is 1.0 g/kg, which correlates with the largest increase in growth performance of S. maximus .